1992
DOI: 10.1085/jgp.99.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen distribution and consumption in the cat retina during normoxia and hypoxemia.

Abstract: Oxygen tension (Po2) was measured with microelectrodes within the retina of anesthetized cats during normoxia and hypoxemia (i.e., systemic hypoxia), and photoreceptor oxygen consumption was determined by fitting Po~ measurements to a model of steady-state oxygen diffusion and consumption. Choroidal Po 2 fell linearly during hypoxemia, about 0.64 mmHg/mmHg decrease in arterial Po~ (Pao~). The choroidal circulation provided ~91% of the photoreceptors" oxygen supply under dark-adapted conditions during both norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
230
3
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(245 citation statements)
references
References 33 publications
11
230
3
1
Order By: Relevance
“…In the dark-adapted cat retina, QoR (called Qav there) was 4.4 ml 02 (100 g min) -1, and decreased in light adaptation to 60% of the value in dark (Haugh et al, 1990). In other studies in the cat, OoR was 5.1 and 3-9mlo 2(lO0gmin) x in darkness, decreasing to 33 % and 36 % of those values respectively in light adaptation (Linsenmeier and Braun, 1992;. Clearly the effect of light on QoR is similar in toad and in cat, and given the difference in temperature of the retinas, toad at 22°C and cat at 38°C, it was expected that the toad retina would have a lower absolute OO 2 than the cat retina.…”
Section: Retinal Q02mentioning
confidence: 78%
See 1 more Smart Citation
“…In the dark-adapted cat retina, QoR (called Qav there) was 4.4 ml 02 (100 g min) -1, and decreased in light adaptation to 60% of the value in dark (Haugh et al, 1990). In other studies in the cat, OoR was 5.1 and 3-9mlo 2(lO0gmin) x in darkness, decreasing to 33 % and 36 % of those values respectively in light adaptation (Linsenmeier and Braun, 1992;. Clearly the effect of light on QoR is similar in toad and in cat, and given the difference in temperature of the retinas, toad at 22°C and cat at 38°C, it was expected that the toad retina would have a lower absolute OO 2 than the cat retina.…”
Section: Retinal Q02mentioning
confidence: 78%
“…Tissue PO 2 would also be lower in vivo. Evidence from cat retina shows that a modest degree of hyperoxia does not affect retinal QO 2 (Linsenmeier and Yancey, 1989; whereas mild hypoxia could have affected QO 2 (Linsenmeier and Braun, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…of simple models of diffusion difficult. 43 Oxygen levels in the inner retina are higher near arterioles, 25 and in the absence of a choroid, there would be an oxygen concentration gradient favouring oxygen diffusion towards the outer retina across the whole retina. Similarly, it has been shown that in eyes without an inner retinal circulation oxygen diffuses inwards from the choroid across the whole retina in amounts sufficient to meet the metabolic requirements of the normal inner retina.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the partial pressure of oxygen [PO 2 ] at the level of photoreceptors reduces to near zero resulting in a relative hypoxia in this layer compared with other retinal layers. [9][10][11][12] Oxygen consumption by rod photoreceptors…”
Section: What Happens In Dark Adaptationmentioning
confidence: 99%